Efficient usage of adabas replication a practical solution finder - Storr, Dieter W. (Vieweg+Teubner, 2011)
In today's IT organization replication becomes more and more an essential technology. This makes Software AG's Event Replicator for Adabas an important part of your data processing. Setting the right parameters and establishing the best network communication, as well as selecting the efficient target components, is essential for successfully implementing replication. This book provides comprehensive information and unique best-practice experience in the field of Event Replicator for Adabas. It also includes sample codes and configurations making your start very easy. It describes all components necessary to replicate Adabas data successfully, efficiently and securely from the mainframe to Adabas and non-Adabas target databases - located on the mainframe or any open system. The author's comprehensive experience comes from Adabas replication to Windows, primarily on the subscription database and the Reptor engine. This can easily be applied to UNIX and Linux systems. By also providing practical solutions to avoid common problems, the author's experience with mass data replication lets your project become a success story.